Rethinking Marx rethinking the public - John Higgins (Acta Academica, 2014)
This essay argues that the young Marx’s defence of press freedom in the repressive Germany of his day is more important than the tradition of Orthodox Marxism has generally allowed, and is best considered as a crucial constitutive feature of the massively influential career as critical thinker and political activist to come. Furthermore, it is in and through Marx’s reconfiguring of the idea of the public in these early writings that his work may make a significant contribution to today’s mostpressing debates around the practice and elusive ideal of democracy, and notablythose in South Africa involving the so called Freedom of Information bill.